Leading morphological dominants of stroke as a basis for the morbid psychotype in cardiosurgical patients with postoperative hypoxic-ischemic injuries - Mankovskyi , D. (Journal of Education, Health and Sport, 2021)
The study of the structural dominants of stroke as a valid element of the evidence base of the morbid psychotype in cardiosurgical patients with postoperative hypoxic-ischemic injuries is currently a priority. It is mostly due to the actual issues of unresolved problems of patient-oriented strategy of neurological support of cardiosurgical patients, endless contradictions in the tactics of management of this category of patients, frequency and clinical polymorphism of postoperative complications (strokes, encephalopathies, dysfunction, neurosis etc.). Preoperative preparation of patients, transoperative management of patients; issues of premedication, anesthesia; prevention of complications and persistent disabilities, prognosis of efficiency and further quality of life, sometimes social psychoadaptation – all of this require specialists having a deep and comprehensive understanding of the leading components of the nosological prototype, the basic criteria of morphological patterns of the disease. Taking into account the latter, the role and the importance of morphological diagnosis of clinical manifestations is clearly growing among a fairly wide range of complications in cardiac surgery. Aim of research: was to investigate the leading morphological dominants of stroke as a basis for the morbid psychotype in cardiosurgery patients with postoperative hypoxic-ischemic injuries. Material and research methods. Morphological analysis (histological examination) was performed on pieces of brain (gray and white matter), 0.5 cubic cm in size of healthy individuals (infection control, IC, n = 12) and those who belonged to the group of clinical observation, CO, n = 18 (also including thanatological follow-up data from own retrospective annals and archives. The author of the work pays tribute to the bright memory of Professor, Doctor of Medical Sciences A. F. Yakovtsova – Honorary Professor of the Department of Pathological Anatomy, Kharkiv National Medical University, Ministry of Health of Ukraine – for professional consultations during the implementation of this fragment of the dissertation research). The sectional material was carefully removed, pieces with sections of cortical and cerebral matter were separated, and then washed in running water. Fixation was performed for at least 24 hours in 12% formalin solution on phosphate buffer (pH = 7.0-7.2), at t0 =18-200 Co in a glass-ceramic vessel. Dehydration of the material took place through a system of ethyl alcohols solutions from 300 to absolute, poured into resin (paraffin / celloidin according to the needs of the study). From the obtained blocks, using the resources of the microtome “MK-25”, we made a series of histological sections with a thickness of 5-10 μm (in one of three mutually perpendicular planes: frontal, horizontal, sagittal). The obtained sections were stained depending on the research tasks, its strategy, taking into account the type of tissue (hematoxylin-eosin, according to Van Gieson). Histological examination of gray and white matter of the brain was performed by stages. Microscopic analysis of the material was performed using a light optical system of the Lieca microscope (Germany) (x 100; x 300). The cortical and cerebral substances of the cerebral hemispheres and areas of the penumbra were examined. Comparison of control samples with the clinical version was carried out in a comparative aspect. Results. Morphological analysis of native brain preparations samples of healthy individuals, IC (cases of sudden death for the reasons unrelated to pathology of the central and peripheral nervous system) showed in favor of a complete correlation of structural and functional changes with sex-age parameters of postnatal ontogenesis. Gray and white substances are contrast, clearly differentiated, their layers are well marked, they did not contain any signs of foci of inflammation, destructive-degenerative processes, heart attacks and necrosis. The results of the study of the material, from persons belonging to the clinical observation group (ischemic stroke as one of the prototypes of hypoxic-ischemic complications in cardiosurgery patients), showed the presence of ischemic injuries. The latter were characterized by a phased nature, which to some extent depended on the timing of the onset of the stroke phenomenon, the depth of organic damage, microtopography, the volume of areas of destructive and degenerative changes. The foci of edema being inflammatory phenomena and the result of ischemia attracted the attention. The substance of the brain in these loci and adjacent areas is “softened”, brittle, flabby, in a state of dyschromatosis, it is not elastic enough. Some histological preparations observed in the near-term period contained areas of necrosis, with elements of generalizations of ischemic phenomena. Neighboring with damaged areas the fragments of the substance are saturated with leukocyte infiltrates, which are more contrast. Нeart attacks (morphologically thy are trivial focal necrosis) were the leading diagnostic features of ischemic genesis. Conclusion. The pathogenetic scenario of stroke has a number of phases. Its primary leading morphological dominants (as a component of the morbid psychotype of cardiosurgery patients with postoperative hypoxic-ischemic disorders) include the occurrence of focal cerebral infarctions (white, red, mixed). The latter by their nature are necrosis and are caused by ischemia, due to the development of vascular disorders (stasis, thrombosis), lack of blood supply / trophism of the relevant areas of the brain. The final stages of the morphological strategy of stroke are characterized by the appearance of foci of proliferation, astrocytes, collagen fibers, the formation of gliomesodermal, connective tissue scars, cysts.